Critical Period for Weed Control in Grafted and Nongrafted Fresh Market Tomato. Issue 3 (September 2016) - Chaudhari, Sushila; Jennings, Katherine M.; Monks, David W.; Jordan, David L.; Gunter, Christopher C.; McGowen, Samuel J.; Louws, Frank J.
Abstract : Field experiments were conducted to determine the critical period for weed control (CPWC) in nongrafted 'Amelia' and Amelia grafted onto 'Maxifort' tomato rootstock grown in plasticulture. The establishment treatments (EST) consisted of two seedlings each of common purslane, large crabgrass, and yellow nutsedge transplanted at 1, 2, 3, 4, 5, 6, and 12 wk after tomato transplanting (WAT) and remained until tomato harvest to simulate weeds emerging at different times. The removal treatments (REM) consisted of the same weeds transplanted on the day of tomato transplanting and removed at 2, 3, 4, 5, 6, 8, and 12 WAT to simulate weeds controlled at different times. The beginning and end of the CPWC, based on a 5% yield loss of marketable tomato, was determined by fitting log-logistic and Gompertz models to the relative yield data representing REM and EST, respectively. In both grafted and nongrafted tomato, plant aboveground dry biomass increased as establishment of weeds was delayed and tomato plant biomass decreased when removal of weeds was delayed. For a given time of weed removal and establishment, grafted tomato plants produced higher biomass than nongrafted. The delay in establishment and removal of weeds resulted in weed biomass decrease and increase of the same magnitude, respectively, regardless of transplant type. The predicted CPWC was from 2.2 to 4.5 WAT in grafted tomato and from 3.3 to 5.8 WAT in nongrafted tomato. The length (2.3 or 2.5 wk) of the CPWC in fresh market tomato was not affected by grafting; however, the CPWC management began and ended 1 wk earlier in grafted tomato than in nongrafted tomato.